2016
DOI: 10.1209/0295-5075/116/26003
|View full text |Cite
|
Sign up to set email alerts
|

Critical dynamics of classical systems under slow quench

Abstract: PACS 64.60.Ht -Dynamic critical phenomena PACS 05.70.Ln -Nonequilibrium and irreversible thermodynamics PACS 64.60.De -Statistical mechanics of model systems (Ising model, Potts model, field-theory models, Monte Carlo techniques, etc.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…In this article, we have analyzed in detail the nonequilibrium dynamics of a classical system when it is annealed slowly from a disordered phase to the critical point in the framework of a kinetic Ising model and a zero-range process. The Kibble-Zurek argument that explains how the equilibrium is approached with decreasing annealing rate has been verified numerically in various recent studies [8,26,9,10,11]. But it has also been found that this argument overestimates the defect density, and scaling laws different from those predicted by it can be obtained when critical coarsening is taken into account [6].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In this article, we have analyzed in detail the nonequilibrium dynamics of a classical system when it is annealed slowly from a disordered phase to the critical point in the framework of a kinetic Ising model and a zero-range process. The Kibble-Zurek argument that explains how the equilibrium is approached with decreasing annealing rate has been verified numerically in various recent studies [8,26,9,10,11]. But it has also been found that this argument overestimates the defect density, and scaling laws different from those predicted by it can be obtained when critical coarsening is taken into account [6].…”
Section: Discussionmentioning
confidence: 80%
“…We also note that unlike in the Ising model studied in the last section where the correlation function obeys ( 5), here the equations of motion for the mass distribution are nonlinear (due to the fugacity term) and the coefficients are also mass-dependent. When the hop rates are time-independent and given by u(m) = 1 + (b/m), a stationary state exists and exhibits a phase transition from a fluid phase in which particles are homogeneously distributed to a condensate phase where a finite fraction of particles reside in a single mass cluster, as the parameter b is increased keeping the total particle density ρ c constant [34,9]. The stationary state mass distribution is known exactly to be…”
Section: Zero-range Process In Mean-field Geometrymentioning
confidence: 99%
“…where ν /(1 + νz c ) ≈ 0.315. This, however, is not correct in coarsening systems as already discussed in [38,39,42,43], for example.…”
Section: The Kibble -Zurek Mechanismmentioning
confidence: 93%
“…In the present study, we only consider the dynamics above T c (ie t ∈ [0, τ Q ]). Studies of the cooling rate effects on the coarsening dynamics that is at work close and below the critical point, even after annealing, have been presented in [38] for the 2d Ising model, in [39] for the 2d xy model, in [42] for a one-dimensional non-equilibrium lattice gas model with a phase transition between a fluid phase with homogeneously distributed particles and a jammed phase with a macroscopic hole cluster, and in [43,44] for time-dependent dissipative and stochastic Gross -Pitaievskii models relevant to describe micro-cavity polaritons and cold boson gases.…”
Section: Quench To T = T Cmentioning
confidence: 99%
See 1 more Smart Citation